Thomas Hobbes and political thought in Ireland, c.1660-c.1720 the Leviathan released - Ward, Matthew (Oxford historical monographs, 2024)
Thomas Hobbes is now regarded as one of England's greatest political philosophers. This book considers his reception in Ireland, where, it is suggested, the 'Leviathan' was released. In doing so, the book demonstrates the variety and sophistication of political thought in Ireland